2011
DOI: 10.1002/pon.2054
|View full text |Cite
|
Sign up to set email alerts
|

Self‐efficacy and fear of cancer progression during the year following diagnosis of breast cancer

Abstract: Findings that low SE is associated with high FoP can help to improve the treatment of dysfunctional fears in breast cancer patients. As FoP changes only slightly over time, treatment to enhance SE and reduce FoP should be initiated soon after disease disclosure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 39 publications
3
41
0
Order By: Relevance
“…Bandura suggested that reducing individuals' stress reactions, changing their negative emotional states, and correcting misinterpretations of their physical states are ways to enhance self‐efficacy. Furthermore, Melchior et al suggested that, as FOP changes only slightly over time, the efforts to enhance self‐efficacy and intervene FOP soon after the diagnosis are warranted. One example of an effective approach to intervene depression is a brief behavioral activation and problem‐solving therapy, which has been applied to depressed breast cancer patients .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bandura suggested that reducing individuals' stress reactions, changing their negative emotional states, and correcting misinterpretations of their physical states are ways to enhance self‐efficacy. Furthermore, Melchior et al suggested that, as FOP changes only slightly over time, the efforts to enhance self‐efficacy and intervene FOP soon after the diagnosis are warranted. One example of an effective approach to intervene depression is a brief behavioral activation and problem‐solving therapy, which has been applied to depressed breast cancer patients .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also demonstrated the association between self‐efficacy and FOP . Melchior et al examined the association between FOP and general self‐efficacy in a prospective study with breast cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, fear of cancer recurrence in young BCS with children may be especially distressing. Previous research demonstrates that young BCS with children report greater fear of cancer recurrence because of the potential consequences a recurrence could have on their families, their ability to parent and their children's well-being [15,50]. Connell et al [4] noted that the most commonly reported major personal concern in relation to fear of cancer progression and recurrence in a group of young BCS with children was the future welfare of their children.…”
Section: Discussionmentioning
confidence: 99%
“…A demographic factor associated with fear of recurrence is age, as young age in general, and young age at diagnosis is an important predictor of fear of recurrence 127,128 . Sex, education and marital status do not have a clear correlation with fear of recurrence 125,127 , whereas having children seems to be related to higher levels of fear 129 . Among disease-and treatment-related factors, time from diagnosis shows no association with fear of recurrence 125 and progression of the disease shows conflicting results 122,130 .…”
Section: Determinants Of Fear Of Recurrencementioning
confidence: 76%